1999
DOI: 10.1007/s007050050525
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of six cypovirus isolates by cross-hybridisation of their dsRNA genome segments

Abstract: Genetic relationships between the genome segments of six cypovirus (CPV) isolates were analysed by RNA cross-hybridisation. These included three type 1 viruses and single isolates of types 2, 5 and 12, which collectively are identical to those previously compared by serology and electrophoresis [Mertens et al. (1989), J Gen Virol 70: 173-185]. Since only genome segment 10 of three cypovirus types and segments 8 and 9 of a single virus strain (of type 1) have currently been sequenced, this initial study provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…After ingestion of the inclusion bodies by the insect, the alkaline pH and proteinases of the intestinal track break down the polyhedrin and release the virions, which enter and replicate in the cytoplasm of midgut epithelial cells (Mertens et al, 1999(Mertens et al, , 2004bZhang et al, 1999). Most CPV infections produce chronic disease with low mortality although some are pathogenic (Mertens et al, 1999(Mertens et al, , 2004b.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…After ingestion of the inclusion bodies by the insect, the alkaline pH and proteinases of the intestinal track break down the polyhedrin and release the virions, which enter and replicate in the cytoplasm of midgut epithelial cells (Mertens et al, 1999(Mertens et al, , 2004bZhang et al, 1999). Most CPV infections produce chronic disease with low mortality although some are pathogenic (Mertens et al, 1999(Mertens et al, , 2004b.…”
Section: Introductionmentioning
confidence: 98%
“…The RNA segments are composed of plus-strand mRNA and its complementary minus-strand in an end to end based-pair conWguration with the exception of a protruding 5Ј cap on the plus-strand (Furuichi and Miura, 1975). Based on the migration pattern of the genome segments on a 1% agarose or 3-5% polyacrylamide gel, CPVs are classiWed into 17 distinct electrophoretypes (Mertens et al, 1989(Mertens et al, , 1999(Mertens et al, , 2004bPayne and Mertens, 1983;Payne and Rivers, 1976;Shapiro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Different cypovirus "types" were initially identified on the basis of differences in the migration patterns of their genome segments during polyacrylamide gel electrophoresis, i.e., electropherotypes (22). Subsequent studies showed a good correlation between electropherotype and the grouping of strains on the basis of serological properties (18) or RNA cross-hybridization (17,20). It has recently been shown that, in addition to the RNA migration patterns, nucleotide sequences, for example, those of genome segment 10 (Seg-10; the polyhedrin gene), can be used to distinguish different Cypovirus species (20).…”
mentioning
confidence: 99%
“…Sixteen diVerent virus species (Cypovirus-1 to have already been formally recognized within the genus Cypovirus, family Reoviridae (Mertens et al, 2004). These diVerent species can be distinguished by diVerences in the migration patterns of their dsRNAs during electrophoresis, variations in RNA sequences (both in the coding regions and conserved terminal regions) and by antigenic variation in the viral proteins (Mertens et al, 2004(Mertens et al, , 1999Payne and Rivers, 1976). Further Cypovirus species 18,and 19) have been proposed, based on isolates from mosquitoes (CPV-17- Green et al, 2006;Shapiro et al, 2005) and from the winter moth Operophtera brumata (CPV-18 and 19-Graham et al, 2006) that have been characterized and compared to the existing species by electropherotype analysis and sequencing of the viral genome.…”
Section: Introductionmentioning
confidence: 99%